APPROACHES TO THE FORMATION, MANAGEMENT AND IMPLEMENTATION OF THE FINANCIAL ANTI-CRISIS POTENTIAL OF ENTERPRISES - TYURINA, Nila; NAZARCHUK, Tetyana; HURNYTSKY, Oleksandr; ANTONCHYK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Activity in the market economy is always associated with risks and possible negative consequences arising from the influence of external and internal factors, which provoke crisis situations. Operation in crisis conditions requires special management, which is referred to as crisis management. The results of successfully overcoming crisis phenomena directly depend on the effectiveness of crisis management, which requires the involvement of potential opportunities and resources accumulated and formed within the enterprise’s crisis potential. Therefore, it is important to understand the essence and structure of crisis potential, the peculiarities of its formation, as well as to determine its differences from the existing potential of the enterprise and the possible transformations of its components in crisis conditions. Considering the structural similarity between the existing and crisis potentials, as well as the primary cause of the crisis related to the loss of the enterprise’s solvency, the focus of the study will be on the financial component of this potential, which is realized through crisis financial management. The essential and meaningful content of the definition of "anti-crisis potential" has been studied, the key principles of the formulation, which are characteristic of most author’s definitions, have been determined. Formed own definition of anti-crisis potential, considering common key features. The structural filling of anti-crisis potential was analyzed and the financial component was identified as a priority, which is implemented through anti-crisis financial management. The main goal and principles of organization of financial management of the organization are defined. The main causes of financial crises are analyzed, the comparative characteristics of anti-crisis and anti-crisis financial management are performed, and its main features and components are determined. Financial signs that lead to the bankruptcy of enterprises are highlighted. The stages and main requirements for the implementation of the financial mechanism of anti-crisis management are characterized. A structural diagram of the process of implementing the capital structure optimization strategy has been developed as an example of the implementation of the anti-crisis financial management component.